Tantangan Bahasa Arab sebagai Alat Komunikasi di Era Revolusi Industri 4.0 pada Pascasarjana IAIN Tulungagung - Ahmad Nurcholis; Syaikhu Ihsan Hidayatullah (Arabiyatuna : Jurnal Bahasa Arab, 2019)
The Industrial Revolution 4.0 did not only change the life of business, work, and state, but also people, and education, including Arabic education. These changes, give opportunities for any benefits, on the other hand it also provide challenges. For those who are unable to deal with it, they are going to be fail. This article described and analyzed the challenges of Arabic as the language for communication in Industrial Revolution 4.0. How does Islamic State University respond to the revolutionary changes in industry 4.0. The lovers, activists, educators, and the Arabic language users need to take a quick, precise, and well-prepared attitude. Therefore, the researchers explored data in the Graduate Program of IAIN Tulungagung as the campus of Da'wah and Civilization that use Arabic language as the main pillar in realizing the vision. The researchers used qualitative phenomenological approach. The findings showed that the students were not accustomed in applying Arabic, so they could not create the language environment yet. However, it has often been used in official events. It can be concluded that the Graduate Program of Arabic Language Department of IAIN Tulungagung is able to follow the industrial revolution 4.0 supported by some articles that have been published in both national and international journals.